The Role of Consumer Protection Law in Increasing Consumer Trust and Business Actors in Indonesia - Bintang, Hasdiana Juwita (CV Raskha Media Group, 2025)
Consumer protection is a fundamental aspect in shaping a healthy, fair, and competitive business climate. The existence of regulations such as Law Number 8 of 1999 concerning Consumer Protection provides a legal basis to guarantee consumer rights while imposing obligations on business actors to uphold ethical and responsible business practices. This study aims to analyze the role of consumer protection law in increasing consumer trust and business actors in Indonesia. The research method used is a normative juridical approach, with descriptive-analytical techniques, focusing on rules and regulations, the scientific literature, and results of previous research. The results of the study show that the proper application of consumer protection law has a positive impact on consumer trust, as it provides a sense of security when conducting transactions and legal certainty in dispute resolution. In addition, the regulation encourages business actors to improve professionalism by enhancing product quality, transparency of information, and service quality to maintain customer reputation and loyalty. However, the effectiveness of the law's implementation still faces challenges, including weak supervision, low public legal awareness, and a limited role for consumer dispute resolution institutions. Therefore, it is necessary to strengthen legal education, optimize the supervisory system, and digitize the complaint mechanism to enhance the effectiveness of consumer protection implementation in Indonesia. This research also recommends collaboration among the government, business actors, and consumer organizations to strengthen legal protection, accelerate complaint handling, and build a compliance assessment system that encourages healthy, sustainable business competition.